2017
DOI: 10.1007/s00414-017-1562-1
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of aluminum phosphide poisoning using a new analytical approach: forensic application to a lethal intoxication

Abstract: Aluminum phosphide (AlP) is an effective and cheap pesticide that is commonly used worldwide, but it is also a common cause of human poisoning and carries a high mortality rate. AlP reacts with moisture in air, water, and hydrochloric acid in the stomach to produce phosphine (PH) gas. Two routes of exposure are ingestion of AlP and inhalation of phosphine generated by the action of moisture on AlP. Absorbed phosphine is rapidly metabolized into phosphite and hypophosphite. A method is described for the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…Whatever the mechanism(s), the most important goal in poisoning management is to prevent death, which has been ignored by many animal studies of AlP poisoning. Most of them were focused on alleviating symptoms instead of addressing this key issue (5,10,11,27,43,44). Our study, in turn, has identified DHA as a promising treatment for patients poisoned with rice tablets.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Whatever the mechanism(s), the most important goal in poisoning management is to prevent death, which has been ignored by many animal studies of AlP poisoning. Most of them were focused on alleviating symptoms instead of addressing this key issue (5,10,11,27,43,44). Our study, in turn, has identified DHA as a promising treatment for patients poisoned with rice tablets.…”
Section: Discussionmentioning
confidence: 79%
“…It is the most common cause of death among the residents of developing countries such as Iran and India, with the rate of 70-100 %. Death often occurs during the first 12 to 24 h of poisoning (4,5).…”
mentioning
confidence: 99%
“…Aluminum phosphide (ALP) is a highly dangerous pesticide that is popularly referred to in Iran as rice tablets [ 3 , 4 ]. ALP is a common cause of acute poisoning and death in many developing countries, especially in Asia, and it usually has high fatality rates (60-90%) [ 5 - 11 ]. This pesticide was first introduced in India, where roughly 15,000 accidental or intentional poisonings take place annually, with a reported mortality rate of roughly 67% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another article reviewed favorably the headspace gas chromatography coupled with mass spectrometry (HS-GC-MS). According to the authors, it could measure even minute quantities of phosphine gas [8].…”
Section: Discussionmentioning
confidence: 99%